FORMULASI DAN EVALUASI GRANUL DISPERSI PADAT EKSTRAK KITOSAN CANGKANG KEPITING BAKAU (Scylla serrata) DENGAN PERBANDINGAN KITOSAN:PVP K-30 1:2 - Abdullah, Hannah Savitri; Imtihani, Hilya Nur (Akademi Farmasi Indonesia Yogyakarta, 2022)
Background: Mangrove crab shells (Scylla serrata) contain chitosan which functions as an anticholesterol. Chitosan is insoluble in water but soluble in acids such as acetic acid. In the process of increasing the solubility, a solid dispersion system is made. The solid dispersion is then formulated into granules. Objective: The purpose of this study was to determine the physical properties of the solid dispersion chitosan granules (FI) and the physical mixture granules (FII). Methods: The method used for the manufacture of solid dispersions is solvent evaporation using PVP K-30 (1:2) as a carrier. The solid dispersion will be made in the form of granules by wet granulation method which will then evaluate the quality of the granules. Results: From this study, the granule flow rate FI=12.89 g/second, and FII=24.58 g/second. The angle of repose of the granules FI=22,13o, and FII=9,46o. The compressibility and Hausner granule FI ratio were found to be 20% and 1.25; while FII obtained 9.90% and 1.11. The percentage of water content of FI granules is 6.38%, and FII is 2.04%. Conclusion: The formulation in this study was able to produce granules that met the requirements, and there was a significant difference between the physical properties of FI and FII granules.